Phylogenetic Analysis of Some Taxa Belonging To The Family Lamiaceae in Bitlis Province Using RAPD-PCR Technique - Topdemir, Sıraç; Kurşat, Murat; Bozarı, Sedat (My University, 2024)
In this study, the relationship between 54 taxa of 21 genera belonging to the family Lamiaceae, which grow naturally in Bitlis province, was examined. Genetic similarities between taxa were determined by RAPD - PCR technique. According to the results, the genera Phlomis L., Lamium L., Ballota L., Stachys L. and Sideritis L. in the subfamily of Lamioideae were supported by the morphological systematics; whereas, the genera Marrubium L. separated from the group. It was observed that taxa belonging to the genera Nepeta L., Lallemantia Fisch. & C.A. Mey, Melissa L., Prunella L., Origanum L., Satureja L., Clinopodium L., Cyclotrichium (Boiss.) Manden. & Scheng., Mentha L. and Salvia L. from the subfamily Nepeteoideae supported morphological system, but Ziziphora clinopodioides Lam. taxa showed difference. According to similarity matrix, the similarity was found mostly between Clinopodium vulgare L. subsp. arundanum (Boiss.) Nyman and Clinopodium graveolens subsp. rotundifolium (Pers.) Govaerts with the rate of 0.955 and between Salvia verticillata L. subsp. verticillata and Salvia verticillata subsp. amasiaca (Freyn & Bornm.) Bornm. with the rate of 0.934.
Keywords: Lamiaceae; Bitlis; RAPD-PCR; Molecular phylogeny; Taxonomic classification